Targeted insertion of large DNA sequences by homology‐directed repair or non‐homologous end joining in engineered tobacco BY‐2 cells using designed zinc finger nucleases. (19th July 2019) - Schiermeyer, Andreas; Schneider, Katja; Kirchhoff, Janina; Schmelter, Thomas; Koch, Natalie; Jiang, Ke; Herwartz, Denise; Blue, Ryan; Marri, Pradeep; Samuel, Pon; Corbin, David R.; Webb, Steven R.; et al.
Abstract: Targeted integration of recombinant DNA fragments into plant genomes by DNA double‐strand break (DSB) repair mechanisms has become a powerful tool for precision engineering of crops. However, many targeting platforms require the screening of many transgenic events to identify a low number of targeted events among many more random insertion events. We developed an engineered transgene integration platform (ETIP) that uses incomplete marker genes at the insertion site to enable rapid phenotypic screening and recovery of targeted events upon functional reconstitution of the marker genes. The two marker genes, encoding neomycin phosphotransferase II ( nptII ) and Discosoma sp . red fluorescent protein ( DsRed ) enable event selection on kanamycin‐containing selective medium and subsequent screening for red fluorescent clones. The ETIP design allows targeted integration of donor DNA molecules either by homology‐directed repair (HDR) or non‐homologous end joining (NHEJ)‐mediated mechanisms. Targeted donor DNA integration is facilitated by zinc finger nucleases (ZFN). The ETIP cassette was introduced into Nicotiana tabacum BY‐2 suspension cells to generate target cell lines containing a single copy locus of the transgene construct. The utility of the ETIP platform has been demonstrated by targeting DNA constructs containing up to 25‐kb payload. The success rate for clean targeted DNA integration was up to 21% for HDR and up to 41% for NHEJ based on the total number of calli analyzed by next‐generation sequencing (NGS). The rapid generation of targeted events with large DNA constructs expands the utility of the nuclease‐mediated gene addition platform both for academia and the commercial sector.